Mechanics of rubber bearings for seismic and vibration isolation - Kelly, James M. (Wiley, 2011)
"Mechanics of Rubber Bearings for Seismic and Vibration Isolation collates in a compact form all of the information on the mechanics of the increasingly important technology of multi-layer rubber bearings. It explores a unique & comprehensive combination of relevant topics, covering all prerequisite fundamental theory and providing a number of closed form solutions to various boundary value problems as well as a comprehensive historical overview on the use of this technique.The authors progress logically through increasingly complex analyses; many of the results presented are new and are needed for a proper understanding of these bearings and for the design and analysis of vibration isolation or seismic isolation systems. The advantages afforded by adopting these natural rubber systems"otheir cost effectiveness, simplicity, and reliability"is clearly explained to designers and users of this emerging technology, bringing into focus the design and specification of bearings for buildings, bridges and industrial structures"--